Wybrane problemy źródeł prawa - Piotrowski, Artur; Kozłowski, Tomasz; Piszko, Robert; Kordela, Marzena (Wydział Prawa i Administracji UAM, 1994)
Those papers concern selected issues taken from the area of the origin of the law and the legal system. The authors consider relations between changes in the concepts of the origin of law and formal transformations of the legal system. A. Piotrowski stresses an increasing number of judicial decisions in the Polish statutory law, which in consequence blur the sharp line between the making and the execution of law. T. Kozłowski describes difficulties which are currently encountered in the process of the law-making in the light of a collapse of the authority of the law, and postulates a detailed research into that phenomenon. R. Piszko provides a global characteristics of the relations between the legal system and other systems outside that system, operating in the same environment and argues that concepts in that area should be precisely defined. M. Kordela discusses the role of ombudsman in Poland in the reconstruction process of legal principles (material, formal and institutional) on which a concept of legal state, and the contents of its concept are based.
Selected problems from the area of origins of law